2020
DOI: 10.1242/dev.197590
|View full text |Cite
|
Sign up to set email alerts
|

Defining compartmentalized stem cell populations with distinct cell division dynamics in the ocular surface epithelium

Abstract: Adult tissues contain label-retaining cells (LRCs) which are relatively slow-cycling and considered to represent a property of tissue stem cells (SCs). In the ocular surface epithelium, LRCs are present in the limbus and conjunctival fornix; however, the character of these LRCs remains unclear due to lack of appropriate molecular markers. Using three CreER transgenic mouse lines, we demonstrate that the ocular surface epithelium accommodates spatially-distinct populations with different cell division dynamics.… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 71 publications
1
7
0
Order By: Relevance
“…Slow‐cycling SCs express Dlx1 , while fast‐cycling SCs express Slc1a3 . Similar SCs heterogeneity and compartmentalization have also been described in the human skin (Ghuwalewala et al , 2022) and the eye epithelium (Ishii et al , 2020; Altshuler et al , 2021; Farrelly et al , 2021). Slow‐ and fast‐cycling SCs undergo distinct differentiation programs to give rise to the keratin (K)10+ interscale and K31+ scale structures of the tail skin, respectively (Gomez et al , 2013; Sada et al , 2016).…”
Section: Introductionsupporting
confidence: 63%
“…Slow‐cycling SCs express Dlx1 , while fast‐cycling SCs express Slc1a3 . Similar SCs heterogeneity and compartmentalization have also been described in the human skin (Ghuwalewala et al , 2022) and the eye epithelium (Ishii et al , 2020; Altshuler et al , 2021; Farrelly et al , 2021). Slow‐ and fast‐cycling SCs undergo distinct differentiation programs to give rise to the keratin (K)10+ interscale and K31+ scale structures of the tail skin, respectively (Gomez et al , 2013; Sada et al , 2016).…”
Section: Introductionsupporting
confidence: 63%
“…The transparent cornea is unique in the sense that epithelial cells are exposed to harmful conditions that include sun irradiation, toxicants, injuries, and infections (Secker and Daniels, 2008). The clarity and high accessibility of the cornea, however, allow robust SC lineage tracing (Amitai- Lange et al, 2015aLange et al, , 2015bDi Girolamo et al, 2015;Dora `et al, 2015) and SC depletion using simple vital microscopy (Nasser et al, 2018;Park et al, 2019;Ishii et al, 2020). Corneal epithelial SCs are known as rare slow-cycling cells that reside in the opaque limbus, a ring-shaped zone at the corneal-conjunctival boundary (Cotsarelis et al, 1989;Sartaj et al, 2017;Ebato et al, 1988;Pellegrini et al, 1999).…”
Section: Introductionmentioning
confidence: 99%
“…Differentiating cells exit the cell cycle and migrate apically through the stratified corneal epithelium, which includes layers of suprabasal wing cells and the most superficial squamous cells. Recently, studies have demonstrated that there may be another noncanonical pathway of differentiation that gives rise to differentiated cells that extend circumferentially around the limbus ( 5 7 ).…”
mentioning
confidence: 99%